Meso-Rex bypass shunt vs. transposition shunt for cavernous transformation of portal vein in children - Lv, Yong; Pu, Lihui; Song, Jiulin; Yang, Jian; Zou, Guoyou; Yang, Jiayin; Xiang, Bo; Jin, Shuguang (Frontiers in Pediatrics, 2022)
Background Cavernous transformation of the portal vein (CTPV) causes portal hypertension in children. Among Meso-Rex treatments, it is unclear whether the Meso-Rex bypass shunt (MRB) or the Meso-Rex transposition shunt (MRT) offers lower postoperative morbidity. Our objective was to evaluate postoperative outcomes, comparing MRB and MRT for children with CTPV. Methods A retrospective study was conducted on children undergoing Meso-Rex for CTPV from January 2010 to December 2020. The primary outcome was shunt complications, including shunt stenosis and thrombus. The secondary outcome was re-operation. Results Of the 43 patients included, 21 underwent MRT and 22 underwent MRB. MRT was associated with a higher rate of shunt complications when compared to MRB (23.8 vs. 9.1%, p = 0.191). The patients exhibited a higher rate of re-operation under the MRT than under the MRB (19 vs. 4.5%, p = 0.138). The operative time in the MRT group was significantly shorter than in the MRB group. Compared to MRT, the reduction in the length and thickness of the spleen was significantly greater in the MRB group. The increases in platelets were significantly higher in the MRB group than in the MRT group. The postoperative shunt velocity of MRB was notably faster than MRT. There was no significant difference in postoperative portal pressure between the two groups (p > 0.05). Conclusion Both MRB and MRT result in acceptable postoperative outcomes, but MRT is associated with higher post-shunt complications, which often increase the re-operation rate. This study suggests that MRB may offer advantages for children with CTPV.